Structural brain correlates of externalizing traits and symptoms in the IMAGEN sample - Phillips, Nathaniel L.; Sharpe, Brinkley M.; Hyatt, Courtland S.; Owens, Max M.; Carter, Nathan T.; Lynam, Donald R.; Banaschewski, Tobias; Bokde, Arun L. W.; Barker, Gareth; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; et al. (Personality disorders, 2025)
The evidence supporting the presence of individual brain structure correlates of the externalizing spectrum (EXT) is sparse and mixed. To date, large-sample studies of brain-EXT relations have mainly found null to very small effects by focusing exclusively on either EXT-related personality traits (e.g., Hyatt et al., 2022) or EXT-related disorders/symptoms (e.g., Mewton et al., 2022). In this preregistered study using IMAGEN data (N = 1,370), we investigated the structural brain correlates of EXT factors that comprise both personality (e.g., antagonism) and psychopathology constructs (e.g., conduct disorder) across levels of morphometric specificity. Brain morphometry was operationalized in terms of omnibus measures (e.g., total brain volume), subcortical volume, and Desikan atlas regions (N = 161 structural magnetic resonance imaging metrics). We operationalized our integrated personality-psychopathology EXT through exploratory factor analyses of EXT-related measures, which identified two dimensions—nonsubstance use and substance use—and one overarching EXT domain. The results were consistent with previous large-sample neuroscientific investigations of EXT: The vast majority of relations were null, and all effect sizes were very small (largest marginal R² < .02). Preregistered supplementary analyses indicated that all significant relations found were driven by total intracranial volume and sex of the participant and became nonsignificant following the inclusion of these covariates. We conclude with suggestions regarding the importance of relevant covariates and large samples in clinical neuroscientific investigations. (PsycInfo Database Record (c) 2025 APA, all rights reserved)